# p(x) = 6x² – 7x + 2

## Answers

Answered by

3

**Answer:**

p(x) = 6x² – 7x + 2

= 6x² -(4x+3x) + 2

= 6x² - 4x - 3x + 2

= 2x(3x - 2) - 1(3x-2)

= (3x-2)(2x-1)

## follow me on brainly

Answered by

1

**Step-by-step explanation:**

We can Split the Middle Term of this expression to factorise it

In this technique, if we have to factorise an expression like

a

x

2

+

b

x

+

c

, we need to think of 2 numbers such that:

N

1

⋅

N

2

=

a

⋅

c

=

6

⋅

2

=

12

AND

N

1

+

N

2

=

b

=

7

After trying out a few numbers we get

N

1

=

3

and

N

2

=

4

3

⋅

4

=

12

, and

3

+

4

=

7

6

x

2

+

7

x

+

2

=

6

x

2

+

3

x

+

4

x

+

2

=

3

x

(

2

x

+

1

)

+

2

(

2

x

+

1

)

2

x

+

1

is a common factor to each of the terms

=

(

2

x

+

1

)

(

3

x

+

2

mark me as brainliest

Similar questions